Does the feeding strategy enhance the aerobic granular sludge stability treating saline effluents?. (July 2019) - Carrera, P.; Campo, R.; Méndez, R.; Di Bella, G.; Campos, J.L.; Mosquera-Corral, A.; Val del Rio, A.
Abstract: The development and stability of aerobic granular sludge (AGS) was studied in two Sequencing Batch Reactors (SBRs) treating fish canning wastewater. R1 cycle comprised a fully aerobic reaction phase, while R2 cycle included a plug-flow anaerobic feeding/reaction followed by an aerobic reaction phase. The performance of the AGS reactors was compared treating the same effluents with variable salt concentrations (4.97–13.45 g NaCl/L) and organic loading rates (OLR, 1.80–6.65 kg CODs/(m 3 ·d)). Granulation process was faster in R2 (day 34) than in R1 (day 90), however the granular biomass formed in the fully aerobic configuration was more stable to the variable feeding composition. Thus, in R1 solid retention times (SRT), up to 15.2 days, longer than in R2, up to 5.8 days, were achieved. These long SRTs values helped the retention of nitrifying organisms and provoked the increase of the nitrogen removal efficiency to 80% in R1 while it was approximately of 40% in R2. However, the presence of an anaerobic feeding/reaction phase increased the organic matter removal efficiency in R2 (80–90%) which was higher than in R1 with a fully aerobic phase (75–85%). Furthermore, in R2 glycogen-accumulating organisms (GAOs) dominated inside the granules instead of phosphorous-accumulating organisms (PAOs), suggesting that GAOs resist better the stressful conditions of a variable and high-saline influent. In terms of AGS properties an anaerobic feeding/reaction phase is not beneficial, however it enables the production of a better quality effluent. Graphical abstract: Image 1 Highlights: Fully aerobic or anaerobic-fed SBR to study aerobic granular sludge stability. Granulation is faster in the anaerobic-fed SBR than in the fully aerobic one. Granules from the fully aerobic SBR are more stable to load and salinity variations. Anaerobic-fed SBR has better COD removal and fully aerobic SBR has better N removal. The low P/COD ratio and composition variation promoted GAO enrichment.